2009
DOI: 10.1016/j.cub.2009.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Noise Pollution Changes Avian Communities and Species Interactions

Abstract: Humans have drastically changed much of the world's acoustic background with anthropogenic sounds that are markedly different in pitch and amplitude than sounds in most natural habitats. This novel acoustic background may be detrimental for many species, particularly birds. We evaluated conservation concerns that noise limits bird distributions and reduces nesting success via a natural experiment to isolate the effects of noise from confounding stimuli and to control for the effect of noise on observer detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
499
1
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 544 publications
(528 citation statements)
references
References 34 publications
17
499
1
11
Order By: Relevance
“…Most studies of anthropogenic sound focus on the direct individual‐level (e.g., physiological stress) or population‐level (e.g., mate‐finding) effects, with relatively few examples of community‐level indirect effects. Studies have suggested that anthropogenic sounds could alter interactions between predators and prey through mechanisms including antipredator behavior and vigilance (e.g., (Francis et al., 2009; Wale, Simpson, & Radford, 2013; Rabin, Coss, & Owings, 2006)). However, our study uniquely shows that anthropogenic sounds can alter predation rates and indirectly affect prey abundance and plant biomass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of anthropogenic sound focus on the direct individual‐level (e.g., physiological stress) or population‐level (e.g., mate‐finding) effects, with relatively few examples of community‐level indirect effects. Studies have suggested that anthropogenic sounds could alter interactions between predators and prey through mechanisms including antipredator behavior and vigilance (e.g., (Francis et al., 2009; Wale, Simpson, & Radford, 2013; Rabin, Coss, & Owings, 2006)). However, our study uniquely shows that anthropogenic sounds can alter predation rates and indirectly affect prey abundance and plant biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic sound is increasingly recognized as a major component of global change in both urban and rural environments (Buxton et al., 2017), but its consequences for species and their interactions remain relatively unknown. Sound is an important part of many species life histories, and consequently, anthropogenic sounds can disrupt these activities and processes (Barber, Crooks, & Fristrup, 2010; Francis, Ortega, & Cruz, 2009; McMahon, Rohr, & Bernal, 2017). While some studies have explored the effects of noise at the individual or intraspecific level, considerably less is known about how anthropogenic sound can influence interactions among species in a community (McMahon et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Букa кoja мoжe нaстaти приликoм рaдa машина може да утичe нa фaуну, jeр oнeмoгућуje стaлaн бoрaвaк живoтињa и утиче на помјерање извaн домета извoрa букe (Barber, et al, 2011;Francis, et al, 2009). Будући да ће се током реконструкције употребљавати већи број грађевинских машина и транспортних средстава која производе буку, ниво буке може трајно или повремено прелазити уобичајен ниво допуштене буке на граници стамбене зоне, од 45 dBA.…”
Section: очекивани утицаји током изградњеunclassified
“…In particular, the latter seems to be challenging for urban birds as the noise interferes with avian acoustic communication, has the potential to change species composition, and may cause serious fitness consequences (Francis et al. 2009; González‐Oreja et al. 2012; Schroeder et al.…”
Section: Introductionmentioning
confidence: 99%